Salinity gradient power: Optimization of nanopore size. (20th November 2016) - Tseng, Shiojenn; Li, Yu-Ming; Lin, Chih-Yuan; Hsu, Jyh-Ping
Graphical abstract: Abstract: Taking account of the effect of diffusioosmotic flow, the salinity gradient power based on reverse electrodialysis is simulated by considering a nanopore connecting two identical, large reservoirs filled with an aqueous sodium chloride solution having different concentrations. The influences of the nanopore radius and length, and the salt gradient across it on the maximum retrievable power density and the efficiency at that power density are examined. For both a negatively and a positively charged nanopore, a larger power density can be obtained by choosing a narrower and/or shorter nanopore, and a larger salt gradient, in general. In contrast, a narrower and/or longer nanopore, and a smaller salt gradient should be adopted for a higher efficiency. The performance of a positively charged nanopore is better than that of a negatively charged one because it is easier for counterions to diffuse through in the former, thereby enhancing both power and efficiency. Regression relationships for the dependence of the maximum power density and the corresponding efficiency on the radius and length of a nanopore, and the salt gradient across it are recovered for design purposes.